Relationship between oxidized low-density lipoprotein antibodies and obesity in different glycemic situations - Babakr AT (Dove Medical Press, 2014)
Abdullatif Taha Babakr,1 Osman Mohamed Elsheikh,2 Abdullah A Almarzouki,3 Adel Mohamed Assiri,1 Badr Eldin Elsonni Abdalla,4 Hani Yousif Zaki,5 Samir H Fatani,1 EssamEldin Mohamed NourEldin11Department of Medical Biochemistry, Faculty of Medicine, Umm Al-Qura University, Makkah, Kingdom of Saudi Arabia; 2Department of Biochemistry, Faculty of Medicine, International University of Africa, Khartoum, Sudan; 3Department of Internal Medicine, Faculty of Medicine, Umm Al-Qura University, Makkah, 4Department of Biochemistry, Sciences Faculty for Girls, King Abdulaziz University, Jeddah, Kingdom of Saudi Arabia; 5Department of Biochemistry and Nutrition, Faculty of Medicine, University of Gezira, Sudan Background: Autoantibodies to oxidized low-density lipoprotein (oxLDL) are a heterogeneous group of antibodies that are controversially discussed to be either pathogenic or protective. Biochemical and anthropometric measurements correlated with increased levels of these antibodies are also controversial, especially in conditions of impaired glucose tolerance and type 2 diabetes mellitus. The present study was conducted to evaluate levels of oxLDL antibodies and their correlation with obesity in different glycemic situations. Methods: Two hundred and seventy-four adult males were classified into three subgroups: group 1 (n=125), comprising a control group of nondiabetic subjects; group 2 (n=77), comprising subjects with impaired glucose tolerance; and group 3 (n=72), comprising patients with type 2 diabetes mellitus. Body mass index was calculated, and measurement of oxLDL and oxLDL antibodies was performed. Results: Higher mean concentrations of oxLDL were found in the type 2 diabetes mellitus and impaired glucose tolerance groups (143.5±21.9 U/L and 108.7±23.7 U/L, respectively). The mean value for the control group was 73.5±27.5 U/L (P<0.001). Higher mean concentrations of anti-oxLDL antibodies were observed in the type 2 diabetes mellitus and impaired glucose tolerance groups (55.7±17.8 U/L and 40.4±17.6 U/L, respectively). The mean value for the control group was 20.4±10 U/L (P<0.001). Levels of anti-oxLDL antibodies were found to be positively and significantly correlated with body mass index in the control group (r=0.46), impaired glucose tolerance (r=0.51), type 2 diabetes mellitus group (r=0.46), and in the whole study population (r=0.44; P<0.001). Conclusion: Anti-oxLDL antibody levels were increased in subjects with type 2 diabetes mellitus and impaired glucose tolerance and were positively correlated with obesity and body mass index. Keywords: anti-oxidized low-density lipoprotein antibodies, obesity, body mass index, diabetes, impaired glucose tolerance